2021
DOI: 10.1111/ppc.12789
|View full text |Cite
|
Sign up to set email alerts
|

Energy drink consumption and its relationship to alcohol use disorders and impulsiveness in health sciences students in Turkey

Abstract: Purpose: We aimed to examine energy drink (ED) consumption and its relationship to alcohol use disorders and impulsiveness in health sciences students.Design and Methods: This cross-sectional research was conducted with 1202 health sciences students. Data collection tools were "Energy Drink Consumption Form," "Alcohol Use Disorders Identification Test (AUDIT)," and "Barratt Impulsiveness Scale-11 (BIS-11)."Findings: Of the students, 30.6% who used EDs reported doing so in the past year. AUDIT and BIS-11 scores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…All the studies included male and female subjects with a range of 18–34 years; the sample size ranged from 72 [ 56 ] to 10,340 individuals [ 60 ]. The evaluation of ED consumption frequency is based mainly on a monthly report [ 26 , 30 , 33 , 35 , 38 , 39 , 41 , 45 , 49 , 50 , 52 , 54 , 55 , 59 , 61 , 63 ], less commonly on a yearly report [ 29 , 34 , 37 , 42 , 53 , 60 , 62 , 64 ] and on a weekly report in only two studies [ 23 , 54 ]. Thirteen articles analyzed AmED consumption in comparison with the consumption of alcohol alone [ 24 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 43 , 45 , 46 , 53 ] while four articles compared the AmED consumption with EDs only [ 28 , 29 , 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…All the studies included male and female subjects with a range of 18–34 years; the sample size ranged from 72 [ 56 ] to 10,340 individuals [ 60 ]. The evaluation of ED consumption frequency is based mainly on a monthly report [ 26 , 30 , 33 , 35 , 38 , 39 , 41 , 45 , 49 , 50 , 52 , 54 , 55 , 59 , 61 , 63 ], less commonly on a yearly report [ 29 , 34 , 37 , 42 , 53 , 60 , 62 , 64 ] and on a weekly report in only two studies [ 23 , 54 ]. Thirteen articles analyzed AmED consumption in comparison with the consumption of alcohol alone [ 24 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 43 , 45 , 46 , 53 ] while four articles compared the AmED consumption with EDs only [ 28 , 29 , 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…As for the quality assessment, a total of 25 articles showed a poor quality rating, which means with important limitations that could invalidate the results and high risk of bias in general [ 23 , 24 , 25 , 26 , 27 , 31 , 34 , 36 , 38 , 40 , 41 , 43 , 44 , 45 , 46 , 47 , 48 , 55 , 56 , 57 , 58 , 60 , 61 , 62 , 63 , 64 ]. A total of 15 assessed studies reported a fair quality rating, with no known important limitation that could invalidate the results and with a moderate or acceptable risk of bias [ 28 , 29 , 30 , 35 , 37 , 42 , 49 , 50 , 51 , 52 , 53 , 54 , 58 , 61 ] and only two studies reported a good quality rating with all criteria met and a very low risk of bias [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations